Islam Dan Peradaban Persia: Integrasi Budaya Dan Keilmuan Pada Masa Dinasti Abbasiyah - Sabda Maulana; Tenny Sujatnika (Jurnal Teologi Islam, 2025)
The Abbasid Caliphate represents one of the most remarkable periods in Islamic civilization, characterized by the integration of cross-cultural elements, particularly Persian intellectual traditions. Persian culture was not merely a complementary component but a foundational force in shaping Islamic governance, education systems, and scientific advancements. Institutions such as the Bayt al-Hikmah (House of Wisdom) facilitated large-scale translations and the development of knowledge from Persian, Greek, and Indian sources, creating a cosmopolitan and intellectually vibrant environment. Persian scholars like Al-Khwarizmi, Ibn Sina, and Al-Farabi made groundbreaking contributions in various scientific fields, which continue to influence modern scholarship. This article examines the role of Persian culture and knowledge in shaping the unique character of the Abbasid civilization, highlighting its influence in administration, literature, arts, and classical Islamic sciences.